2011
DOI: 10.1097/tp.0b013e3181fa94b9
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Renal Function in Children After Liver Transplantation

Abstract: This study underlines the importance of long-term renal function surveillance after LT performed on children. Although measuring GFR remains the preferred function surveillance method, the updated Schwartz formula is also acceptable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
47
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 31 publications
(35 reference statements)
9
47
1
Order By: Relevance
“…As previously shown (23,24), the bedside Schwartz formula overestimated the GFR by 10% on average. This is in agreement with a report by Tsampalieros et al (23), who found that in kidney transplant recipients the bedside Schwartz formula overestimated the mGFR by 9%.…”
Section: Discussionsupporting
confidence: 54%
“…As previously shown (23,24), the bedside Schwartz formula overestimated the GFR by 10% on average. This is in agreement with a report by Tsampalieros et al (23), who found that in kidney transplant recipients the bedside Schwartz formula overestimated the mGFR by 9%.…”
Section: Discussionsupporting
confidence: 54%
“…The complications of long-term use of immunosuppression are-among others-nephrotoxicity and cancer risk. Chronic kidney disease was found in 25% to 30% at 10 years after OLT [34,35]. The use of newer and less nephrotoxic immunosuppressive agents such as tacrolimus might be associated with better long-term kidney function, although the long-term evaluation of the randomized European trial of cyclosporin vs tacrolimus in pediatric OLT revealed no difference between both groups [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…However, availability of high quality donor livers for hepatocyte isolation is limited. Furthermore, transplantation of allogeneic hepatocytes does not bypass the need for long-term immunotherapy, which is by itself one important factor in the reduced life expectancy of PH1 patients (Cibrik et al 2002;Kivelä et al 2011). Consequently, current efforts are targeted at the potential use of hepatocytes generated from iPSCs derived from individual patients as vehicles for ex vivo gene therapy using autologous cells (Zapata-Linares et al 2016), so that the need for immunosuppression can be circumvented.…”
Section: Cell Therapymentioning
confidence: 97%